Menilai efektivitas dan efisiensi dari akuntansi forensik dan audit investigasi terhadap pembuktian kecurangan - Rony Uncok Cahyadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of this study to analyze the effectiveness and efficiency of forensic accounting and investigative audits to prove the occurrence of fraud in an organization. The research method used in this study is a qualitative method with a literature review approach. The data used in this study is secondary data based on the results of research that has been conducted previously, by comparing research that produces conclusions as expected in this study with research that produces different conclusions. In general, the results of this research can be concluded that the use of forensic accounting and investigative audits effectively and efficiently can help organizations to identifying and detecting fraud has occurred in an organization, and can also be validly proven. This happens because the use of forensic accounting and investigative audits is the most appropriate, accurate and correct way to help organizations prove that fraud has occurred.